Wounds That Heal: A Photovoice Study of Post-Traumatic Growth Among Women Survivors of Domestic Violence Following Divorce - Eduardus Julio Angga Huky; M. K. P. Abdi Keraf; Rizky Pradita Manafe; Yeni Damayanti (Universitas Nusa Cendana, 2026)
Introduction Domestic Violence has become a widespread issue in society, including Kupang City, with women being the primary victims. Incidents of domestic violence have both physical and psychological impacts on victims, resulting in traumatic experiences. Some women who experience domestic violence choose to divorce. Although research generally reports negative psychological adjustment among female survivors after divorce due to domestic violence, survivors may also demonstrate positive changes in their lives following the crisis caused by trauma. Aim This study explores the forms and processes of Post-Traumatic Growth among divorced female survivors of domestic violence in the city of Kupang. Result Thematic analysis identified five major themes: the dynamics of divorce, self-reflection, the strength to survive, rising from adversity, and making peace with life's circumstances. Conclusion The findings indicate that although the survivors experienced traumatic events, there remained opportunities for positive personal growth through a process of self-reflection, ultimately leading to acceptance of the life circumstances they faced after divorcing due to domestic violence.